2022
DOI: 10.3847/1538-4357/ac59b7
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Wave–Particle Interactions in Collisionless Plasmas: Theory and Its Application to the Alfvén-mode Wave

Abstract: Wave–particle interactions can induce energy transfer at different timescales in collisionless plasmas, which leads to the reshaping of the particle velocity distribution function. Therefore, how to quantify wave–particle interactions is one of the fundamental problems in the heliosphere and in astrophysical plasmas. This study proposes a systematic method to quantify linear wave–particle interactions based on the Vlasov–Maxwellian model. We introduce energy transfer rates with various expressions by using per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Nevertheless, the lack of whistlers observed by Parker Solar Probe for low heliospheric distances <30 Rs suggests that the modification of the electron VDF associated with the ambipolar electric field or changes in other plasma properties must result in lower instability limits for the other modes (including the observed solitary waves and ion acoustic waves) that are observed close to the Sun (Cattell et al, 2022). Resonant and non-resonant wave-particle interactions can induce energy transfer at different timescales in collisionless plasmas, which leads to the reshaping of the particle VDF, as recently quantified by Zhao et al (2022) for typical Alfvén mode waves. Proton VDFs can also be modified by waves, as shown by Voitenko and Pierrard (2015) revealing the influence of kinetic Alfvén waves in the formation of the proton tails and beams.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, the lack of whistlers observed by Parker Solar Probe for low heliospheric distances <30 Rs suggests that the modification of the electron VDF associated with the ambipolar electric field or changes in other plasma properties must result in lower instability limits for the other modes (including the observed solitary waves and ion acoustic waves) that are observed close to the Sun (Cattell et al, 2022). Resonant and non-resonant wave-particle interactions can induce energy transfer at different timescales in collisionless plasmas, which leads to the reshaping of the particle VDF, as recently quantified by Zhao et al (2022) for typical Alfvén mode waves. Proton VDFs can also be modified by waves, as shown by Voitenko and Pierrard (2015) revealing the influence of kinetic Alfvén waves in the formation of the proton tails and beams.…”
Section: Discussionmentioning
confidence: 84%
“…This is due to the fact that exospheric models completely neglect any interactions between the different particles, while solar wind models including Coulomb collisions (Pierrard and Lemaire, 1996) or whistler waves (Pierrard et al, 2011) show that such effects influence the anisotropy of the velocity distribution function, without modifying significantly the average values of the moments. Recent studies of the heat flux instabilities have also shown their effects on the shape of the VDF and especially their anisotropies (Shaaban et al, 2021;Sun et al, 2021;Zhao et al, 2022).…”
Section: Consequences Of Suprathermal Tails At Low Distances On the S...mentioning
confidence: 99%
“…These questions can only be answered by combining theory, simulations, and spacecraft observations. A quantification of the different contributions of instabilities would be worthwhile, as recently provided by Zhao et al (2022) for Alfvén waves in collisionless plasmas. 5.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…The numerical experiments reported here only consider resonant quasilinear diffusion coefficients [e.g., (Lyons et al, 1972;Lyons, 1974)]. However, non-resonant wave-particle interactions [e.g., (Zhao et al, 2022)], although usually much weaker, also depend upon wave amplitudes. For the most intense waves, the nonresonant interaction could be as large as the resonant interaction during typical periods.…”
Section: Temporal Scales Of Variability Leads To Different Levels Of ...mentioning
confidence: 99%